Does offshoring reduce industry employment? - Hijzen, Alexander; Swaim, Paul (Nottingham, 2007)
"This paper looks at the implications of offshoring for industry employment whilst explicitly accounting for the scale and technology effects of offshoring. The effects of offshoring on employment are analysed using industry-level data for 17 high income OECD countries. Our findings indicate that offshoring has no effect or a slight positive effect on sectoral employment. Offshoring within the same industry (“intra-industry offshoring”) reduces the labour-intensity of production, but does not affect overall industry employment. Inter-industry offshoring does not affect labour-intensity, but may have a positive effect on overall industry employment. These findings suggest that the productivity gains from offshoring are sufficiently large that the jobs created by higher sales completely offset the jobs lost by relocating certain production stages to foreign production sites."